La ciénaga - Borges, Graciela 1941- (The Criterion Collection, 2015)
With a radical take on narrative, disturbing yet beautiful cinematography, and a highly sophisticated use of on- and offscreen sound, Martel turns her tale of a decaying bourgeois family, whiling away the hours of one sweaty, sticky summer, into a cinematic marvel. This visceral take on class, nature, sexuality, and the ways political turmoil and social stagnation can manifest in human relationships is a drama of amazing tactility and one of the great contemporary film debuts
1.85:1 Aspect ratio. - New 4K digital film transfer, approved by director Lucrecia Martel
Orig.: Argentinien, Frankreich, Spanien, Japan 2001
Enth. new interview with Lucrecia Martel ; new interview with filmmaker Andrés de Tella about Martel and the film ; an essay by critic David Oubiña